Hubungan Kemampuan Musikal dengan Kepekaan Sosial pada Masa Dewasa Awal - Rosa Virginia Cindy Pramudia; Dewi Indrileani; Tarisya Maretaura Lesmana; Felix Hansel Raditya Wibowo; Hana Permata Heldisari (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2022)
This study aims to determine whether or not there is a relationship between musical ability and social sensitivity in the early adulthood of students at Fermata Music Course, Antonio School of Music, and Allegretto School of Music Yogyakarta, which totaled 107 students. This research uses a quantitative approach with a type of correlation. The population of this study was all students at Fermata Music Course, Antonio School of Music, and Allegretto School of Music Yogyakarta, with a total of 107 people. The samples in this study were taken by purposive random sampling, with criteria of 20-25 years, so a sample of 30 people was obtained. Data collection was carried out with questionnaire techniques to measure social sensitivity and tests to measure musical ability. Instruments are tested by content validation through expert judgment and construct validation with product moment techniques. With musical talent as the independent variable and social sensitivity as the dependent variable, Pearson's product-moment correlation was applied to analyze the data. According to the determined r value of -0.423 and sig of 0.02, there was a moderately unfavorable and statistically significant link between musical talent and social sensitivity in early adulthood. It means that the higher the musical ability, the lower the social sensitivity, on the contrary, the lower the musical ability, the higher the social sensitivity will be. Penelitian ini bertujuan untuk mengetahui ada atau tidaknya hubungan antara kemampuan musikal dan kepekaan sosial pada masa dewasa awal murid di Fermata Music Course, Antonio School of Music, and Allegreto School of Music Yogyakarta yang berjumlah 107 murid. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis korelasi. Populasi penelitian ini adalah seluruh murid di Fermata Music Course, Antonio School of Music, and Allegreto School of Music Yogyakarta dengan jumlah 107 orang. Sampel dalam penelitian ini diambil secara purposive random sampling, dengan kriteria 20-25 tahun sehingga diperoleh sampel sebanyak 30 orang. Pengumpulan data dilakukan dengan teknik angket untuk mengukur kepekaan sosial dan tes untuk mengukur kemampuan musikal. Instrumen diuji dengan validasi isi melalui expert judgement dan validasi konstruk dengan teknik product moment. Dengan bakat musik sebagai variabel independen dan kepekaan sosial sebagai variabel dependen, korelasi product moment pearson digunakan untuk menganalisis data. Berdasarkan nilai r yang ditentukan sebesar -0,423 dan sig 0,02, terdapat hubungan yang cukup tidak menguntungkan dan signifikan secara statistik antara bakat musik dan kepekaan sosial pada masa dewasa awal. Ini berarti semakin tinggi kemampuan musikal maka akan semakin rendah kepekaan sosialnya, sebaliknya semakin rendah kemampuan musikal maka akan semakin tinggi pula kepekaan sosialnya.